2019
DOI: 10.1021/acs.jced.9b00799
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Barium Sulfate Deposition Inhibition and the Prediction of Inhibitor Dosage

Abstract: Scale inhibitors are widely used to prevent mineral scale deposition and precipitation in industrial processes. In this study, the performance of scale inhibitors is systematically investigated in a flow loop apparatus, designed to mimic the barite deposition in pipelines. The inhibitors are tested in tubing with and without a precovered barite scale layer. DTPMP (diethylenetriamine-pentamethylene phosphonic acid), PPCA (phosphinopoly carboxylic acid), and SPCA (sulfonated poly­(carboxylic acid)) are the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Furthermore, an experimental study has analyzed the mechanism of barium sulfate deposition inhibition for multiscale inhibitors. 23 This experimental study on barite scale inhibition showed that DETPMP inhibitor has a very high efficiency compared to other classical inhibitors such as phosphinopoly carboxylic acid and sulfonated poly(carboxylic acid), which supports the findings of this theoretical investigation. 23 DETPMP is a classical inhibitor that used a lot for scale inhibition, and it is experimentally proven that it has an excellent performance in inhibiting barite scale.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, an experimental study has analyzed the mechanism of barium sulfate deposition inhibition for multiscale inhibitors. 23 This experimental study on barite scale inhibition showed that DETPMP inhibitor has a very high efficiency compared to other classical inhibitors such as phosphinopoly carboxylic acid and sulfonated poly(carboxylic acid), which supports the findings of this theoretical investigation. 23 DETPMP is a classical inhibitor that used a lot for scale inhibition, and it is experimentally proven that it has an excellent performance in inhibiting barite scale.…”
Section: Resultssupporting
confidence: 85%
“… 23 This experimental study on barite scale inhibition showed that DETPMP inhibitor has a very high efficiency compared to other classical inhibitors such as phosphinopoly carboxylic acid and sulfonated poly(carboxylic acid), which supports the findings of this theoretical investigation. 23 DETPMP is a classical inhibitor that used a lot for scale inhibition, and it is experimentally proven that it has an excellent performance in inhibiting barite scale. 20 , 21 , 29 Moreover, the theoretical studies provide insights into why DETPMP has a superior performance compared to the other two inhibitors, PASP and NTMP.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…An antiscalant evidently retarded gypsum deposition from supersaturated aqueous solution, obtained by mixing calcium and sulfate brines at ambient temperature. But contrary to popular view, [3,5–9,14] that an antiscalant interacts with the gypsum nuclei, “shielding” them from calcium and sulfate ions sorption, no any interaction of HEDP‐F and CaSO 4 ⋅ 2H 2 O crystals was fixed, Figure 2a. The typical colorless stick‐like gypsum crystals grew up on their own, while HEDP‐F formed its own separate solid phase as calcium salt Ca‐HEDP‐F (blue spherical particles), Figure 2b, c. Some Ca‐HEDP‐F particles, detected on gypsum crystals surfaces, are likely to reflect a coalescence of both phases.…”
Section: Recent Findings Based On Scale Inhibitor Molecules Visualizationmentioning
confidence: 82%
“…A widely used solution for controlling scale deposition is an application of chemical inhibitors: polycarboxylates, phosphonates, some natural “green” additives [2] . However, irrespective of an enduring and successful antiscalant application, the mechanisms of calcium carbonate and gypsum scale inhibition still remain the matter of discussion [3–10] . At the same time, an intensive work has been performed recently worldwide in order to obtain new, more efficient scale inhibitors [11] .…”
Section: Introductionmentioning
confidence: 99%